2015
DOI: 10.3109/11038128.2014.982172
|View full text |Cite
|
Sign up to set email alerts
|

Amount and type of everyday technology use over time in older adults with cognitive impairment

Abstract: Over time, a decreasing use of ET was shown in this sample with MCI. This process was influenced by several aspects important to consider in occupational therapy intervention planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
3
17
1
Order By: Relevance
“…For example, our findings show that persons with cognitive impairment may have a need and/or desire to update their technology use, while simultaneously striving towards downsizing. This nuances our earlier findings regarding use of less ET objects over time in the sample with MCI [ 21 ] of which these participants are a part. It also challenges the commonly held stereotype image of older people with cognitive impairments as being uninterested in updated technology, and has implications for health-care practitioners (such as occupational therapists) and providers of assisted living technologies.…”
Section: Discussionsupporting
confidence: 84%
“…For example, our findings show that persons with cognitive impairment may have a need and/or desire to update their technology use, while simultaneously striving towards downsizing. This nuances our earlier findings regarding use of less ET objects over time in the sample with MCI [ 21 ] of which these participants are a part. It also challenges the commonly held stereotype image of older people with cognitive impairments as being uninterested in updated technology, and has implications for health-care practitioners (such as occupational therapists) and providers of assisted living technologies.…”
Section: Discussionsupporting
confidence: 84%
“…The ability to use assistive technology may also vary. Over time, a decreasing use of technology is seen in people with cognitive impairment [61]. …”
Section: Resultsmentioning
confidence: 99%
“…On the basis of literature review, the research studies concerning the use of mobile phones and/ or smartphones by patients with dementia can be divided into several areas according to their focus as follows:  studies concentrating on the adoption and usability of these devices by patients with dementia; [6,[8][9][10][11]]  descriptive studies depicting the development of potential mobile phone/ smartphone apps for patients with dementia; [12][13]  studies exploring the role of these mobile devices for the assessment and diagnostic purposes; [14-16]  studies focusing on the actual use of mobile phones and/ or smartphones by patients with dementia. [17][18][19] Thorpe et al [6] explored the adoption of smartphone and smartwatch use among people with mild dementia.…”
Section: Findings and Their Discussionmentioning
confidence: 99%
“…For example, Faucounau et al [19] claim that it is a must to involve end-users in the co-design of new technologies in order to develop tailored devices. Furthermore, Hedman et al [10] on the amount and type of everyday technology use found out that people with cognitive impairment tended to decrease the use of everyday technology over time. This is quite common since patients with dementia are generally older people and they like to use what they already know.…”
Section: Findings and Their Discussionmentioning
confidence: 99%